Progress in Nondestructive Detection Techniques for Internal Defects of Agro-products - Rong PENG; Zhenzhen LÜ; Xuan LUO; Wen ZHANG (Shipin gongye ke-ji)
Internal defects can easily develop during the growth process of agro-products, significantly affecting their economic value. Early identification of internal defects is crucial for ensuring the commercial value and safety of agro-products. With the development of nondestructive detection technologies, the methods based on optical, thermal, acoustic, and electromagnetic properties have gradually been applied to the detection of internal defects in agro-products in recent years. This paper reviews the principles and characteristics of the nondestructive detection technologies and their research advancements in detecting internal defects in ago-products and introduces the applications of multi-technology fusion and artificial intelligence in the nondestructive detection. Finally, the challenges of these technologies, along with the future development trends and research directions are also discussed. This paper aims to provide a valuable reference for research on nondestructive detection technologies for internal defects in agro-products.